2019
DOI: 10.3389/fpsyg.2019.02223
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing Self and Other and Affect Regulation Patterns in Anorexia and Depression

Abstract: The study aimed to examine two constructs: general mentalizing processes and the specific component of affective mentalizing regarding self and others alongside the construct of affect regulation patterns in female adolescent and young adult inpatients with anorexia nervosa (AN; n = 41), depression (n = 20) and controls (n = 53). We further examined the predictive ability of affect regulation to eating-disorder (ED) symptoms beyond that of the mentalizing variables, and their potential role in mediating betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
7
24
0
Order By: Relevance
“…In accordance with some previous evidence (Doba et al 2018;Rothschild-Yakar et al 2019), our study reported an association between high levels of alexithymia and low levels of self-differentiation, thus indicating that alexithymic subjects tend to have difficulty regulating emotions and developing intimate relationships, characterized by a balance between autonomy and intimacy, which results in poor self-differentiation. According to our findings, this correlation may be explained by at least two possible mediation factors: adult attachment and fear of intimacy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with some previous evidence (Doba et al 2018;Rothschild-Yakar et al 2019), our study reported an association between high levels of alexithymia and low levels of self-differentiation, thus indicating that alexithymic subjects tend to have difficulty regulating emotions and developing intimate relationships, characterized by a balance between autonomy and intimacy, which results in poor self-differentiation. According to our findings, this correlation may be explained by at least two possible mediation factors: adult attachment and fear of intimacy.…”
Section: Discussionsupporting
confidence: 92%
“…Due to emotional regulation deficits, alexithymia tends to associate with different psychopathological frameworks (Frewen et al 2008;Greene et al 2020;Precee et al 2017;Prino et al 2019;Westwood et al 2017) and difficulties in interpersonal relationships (Hexel 2003;Lyvers et al 2019;Montebarocci et al 2004). Some evidence suggests that high levels of alexithymia tend to be associated with low levels of self-differentiation (Doba et al 2018;Rothschild-Yakar et al 2019). According to Bowen's theory (Bowen 1978; Kerr and Bowen 1988), self-differentiation is a construct that is expressed on two levels: on the intrapsychic level, differentiation of self is the capacity to balance emotional and intellectual functioning; on the interpersonal level, it is the ability to create intimate, emotional ties with others while remaining on some level independent from them, experiencing both intimacy and autonomy (Bowen 1978; Kerr and Bowen 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is the cognitive-affective polarity, which focuses on aspects related to cognition and emotion. 18 , 19 In essence, mentalization gives individuals the ability to reflect on actions, adopt different perspectives, and respond to the demands of the interpersonal environment without reaching emotional states of dysregulation, thus better dealing with negative thoughts or overwhelming emotional states. 19 Diminished mentalization can lead to a variety of different reactions.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 In essence, mentalization gives individuals the ability to reflect on actions, adopt different perspectives, and respond to the demands of the interpersonal environment without reaching emotional states of dysregulation, thus better dealing with negative thoughts or overwhelming emotional states. 19 Diminished mentalization can lead to a variety of different reactions. For example, a person could experience their thoughts, mental images, or affects in an excessively real way, to the extent that they cease to be mental events.…”
Section: Introductionmentioning
confidence: 99%
“…Adding significant knowledge to our understanding of borderline personality disorders (BPD), mentalizing is nowadays going beyond a distinct description of one specific disorder, moving to a transdiagnostic concept [ 6 ]. Reflective functioning was researched in various psychopathologies [ 7 ], including BPD [ 8 ], panic disorder [ 9 ], depression, psychosis [ 10 ], and eating disorders [ 11 ].…”
Section: Introductionmentioning
confidence: 99%